2014
DOI: 10.1016/j.jimonfin.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of international capital flows: Results from a dynamic hierarchical factor model

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 32 publications
1
16
1
Order By: Relevance
“…Other papers have suggested that the effects of shocks on capital flows depend on regional factors. For instance, using a hierarchical factor model, Förster et al (2014) find that the country-specific component explains the largest fraction of fluctuations in capital flows followed by regional factors, while the global factor explains only a smaller part of these fluctuations. Baek (2006) shows that portfolio investment in Latin American economies seems to be pulled mainly by economic growth, while PI in Asian economies is primarily pushed by external factors.…”
Section: Responses Of Disaggregated Capital Flows To Push and Pull Famentioning
confidence: 99%
“…Other papers have suggested that the effects of shocks on capital flows depend on regional factors. For instance, using a hierarchical factor model, Förster et al (2014) find that the country-specific component explains the largest fraction of fluctuations in capital flows followed by regional factors, while the global factor explains only a smaller part of these fluctuations. Baek (2006) shows that portfolio investment in Latin American economies seems to be pulled mainly by economic growth, while PI in Asian economies is primarily pushed by external factors.…”
Section: Responses Of Disaggregated Capital Flows To Push and Pull Famentioning
confidence: 99%
“…See also Förster, Jorra and Tillmann (2012) for an analysis of the global comovement of capital flows.…”
mentioning
confidence: 99%
“…Portfolio investors are yield‐seeking investors that seek risk‐reduction through diversification. A country that is relatively segregated from the rest of the world, with low FDI due to poor governance quality, has a low world beta and provides greater diversification benefits (Aurelio, ; Forster et al ., ). Prior studies (e.g.…”
Section: Background and Hypotheses Developmentmentioning
confidence: 97%